Casting light on Asgardarchaeota metabolism in a sunlit microoxic niche - Bulzu, Paul-Adrian; Andrei, Adrian-Ştefan; Salcher, Michaela M; Mehrshad, Maliheh; Inoue, Keiichi; Kandori, Hideki; Beja, Oded; Ghai, Rohit; Banciu, Horia L (Nature microbiology, 2019)
Recent advances in phylogenomic analyses and increased genomic sampling of uncultured prokaryotic lineages have brought compelling evidence in support of the emergence of eukaryotes from within the archaeal domain of life (eocyte hypothesis)1,2. The discovery of Asgardarchaeota and its supposed position at the base of the eukaryotic tree of life3,4 provided cues about the long-awaited identity of the eocytic lineage from which the nucleated cells (Eukaryota) emerged. While it is apparent that Asgardarchaeota encode a plethora of eukaryotic-specific proteins (the highest number identified yet in prokaryotes)5, the lack of genomic information and metabolic characterization has precluded inferences about their lifestyles and the metabolic landscape that favoured the emergence of the protoeukaryote ancestor. Here, we use advanced phylogenetic analyses for inferring the deep ancestry of eukaryotes, and genome-scale metabolic reconstructions for shedding light on the metabolic milieu of Asgardarchaeota. In doing so, we: (1) show that Heimdallarchaeia (the closest eocytic lineage to eukaryotes to date) are likely to have a microoxic niche, based on their genomic potential, with aerobic metabolic pathways that are unique among Archaea (that is, the kynurenine pathway); (2) provide evidence of mixotrophy within Asgardarchaeota; and (3) describe a previously unknown family of rhodopsins encoded within the recovered genomes.
Keywords: molekulární evoluce; anaerobióza; Genome, Archaeal; ekosystém; Metabolic Networks and Pathways; aerobióza; Aerobiosis; Anaerobiosis; Rhodopsins, Microbial; fylogeneze; Archaea; rhodopsiny mikrobiální; genom archeí; metabolické sítě a dráhy; RNA ribozomální; Ecosystem; Phylogeny; RNA, Ribosomal; Evolution, Molecular